PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA BENGKEL AGUS MOTOR INDRAMAYU JAWA BARAT - Hadi, Wildan; Suworo (Journal of Research and Publication Innovation, 2024)
This study aims to (1) To determine the effect of service quality on customer satisfaction at the Agus Motor Workshop in Indramayu, West Java, (2) To determine the effect of price on customer satisfaction at the Agus Motor Workshop in Indramayu, West Java, (3) To determine the effect of service quality and price simultaneously on customer satisfaction at the Agus Motor Workshop in Indramayu, West Java. The research method used is a quantitative research type. The population in this study were customers who repaired motorbikes at the Agus Motor Workshop in Indramayu, West Java in 2022, which amounted to 7,989 customers, then from this population 99 samples were taken as respondents in this study. The data sources in the study are primary data through surveys, interviews, and questionnaires and secondary data in the form of library studies and documentation. The data analysis methods used in this study consisted of descriptive analysis, validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, and hypothesis test through multiple linear regression, correlation test, determination test, t test and f test. The results of this study are (1) There is a positive and significant influence between service quality and customer satisfaction at Agus Motor Workshop Indramayu West Java, this is evidenced by the simple linear regression equation Y = 3.169 + 0.488 (XI). (2) There is a positive and significant influence between price and customer satisfaction at Agus Motor Workshop Indramayu West Java, this can be evidenced by the simple linear regression equation Y = 4.020 + 0.592 X2. (3) Simultaneously there is a positive and significant influence between service quality and price on customer satisfaction at Agus Motor Workshop Indramayu West Java, this can be evidenced by the multiple linear regression equation Y = 1.340, 0, 281 X1 +0.339 X2. obtained the value of F or (108.779>3.091), this is also reinforced by the value - Sig 0.05 or (0.000 <0.05). Thus, Ho3 is rejected and Ha3 is accepted, this shows that there is a positive and significant influence simultaneously between Service Quality and Price simultaneously on Customer Satisfaction at Agus Motor Workshop Indramayu West Java